God in Proof : the Story of a Search from the Ancients to the Internet. - Schneider, Nathan (University of California Press, 2013)
In this tour of the history of arguments for and against the existence of God, Nathan Schneider embarks on a remarkable intellectual, historical, and theological journey through the centuries of believers and unbelievers-from ancient Greeks, to medieval Arabs, to today's most eminent philosophers and the New Atheists. Framed by an account of Schneider's own unique journey, God in Proof illuminates the great minds who wrestled with one of history's biggest questions together with their arguments, bringing them to life in their time, and our own. Schneider's sure-handed portrayal of the c.